2011
DOI: 10.1016/j.jalz.2011.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Videoconference diagnosis and management of Choctaw Indian dementia patients

Abstract: Background To report a 5-year experience using videoconference (VC) technology to diagnose and treat adult members of the Choctaw Nation with symptoms or complaints of cognitive impairment. Methods Patients were given the option of VC or face-to-face clinic. Prior to their VC session, patients underwent neuropsychological testing, Clinical Dementia Rating, Geriatric Depression Scale and Neuropsychiatric Inventory, brain CT, and routine blood tests. Physical observations made by VC included eyesight, hearing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 33 publications
2
37
0
4
Order By: Relevance
“…Clinicians were able to see the caregivers without having to do home visits, thus increasing the number of caregivers that could be helped in one day (Finkel et al, 2007). Similar results were reported by researchers at the University of Texas who used videoconferencing technology to provide services to patients and families in the Choctaw (Indian) Nation (Weiner, Rossetti, & Harrah, 2011). Another successful example is the computer-mediated automated interactive voice response (IVR) intervention by Mahoney (Mahoney, Tarlow, & Jones, 2003) that was designed to assist family caregivers to manage disruptive behaviors related to the patient's dementia.…”
Section: Telephone/videophone Consultation And/or Treatmentsupporting
confidence: 67%
“…Clinicians were able to see the caregivers without having to do home visits, thus increasing the number of caregivers that could be helped in one day (Finkel et al, 2007). Similar results were reported by researchers at the University of Texas who used videoconferencing technology to provide services to patients and families in the Choctaw (Indian) Nation (Weiner, Rossetti, & Harrah, 2011). Another successful example is the computer-mediated automated interactive voice response (IVR) intervention by Mahoney (Mahoney, Tarlow, & Jones, 2003) that was designed to assist family caregivers to manage disruptive behaviors related to the patient's dementia.…”
Section: Telephone/videophone Consultation And/or Treatmentsupporting
confidence: 67%
“…Powers et al, examined TM for assessing and diagnosis of dementia among rural veterans and found that the no‐show and cancelation rate was 5.4% lower for TM assessments compared with FTF assessments (Powers et al, ). In another study, Weiner et al () found that refusals and no‐show rates for TM assessments were 3% (Weiner et al, ). Three studies, examining acceptability using surveys found that participants would use TM assessments again (Parikh et al, ; Shores et al, ; Vestal et al, ; Wofford et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Rural (Talihina) subjects were diagnosed on site by ADC personnel and/or by teleconference interviews augmented by more detailed on-site neuropsychological testing (which did not include the measures used in this study), CT or MRI scans, and appropriate blood tests (Weiner, Rossetti, & Harrah, 2011). …”
Section: Methodsmentioning
confidence: 99%